Factors contributing to transient-induced fading: Examining the impact of luminance contrasts and subjective contours - Moyou Jiang; Hiroyuki Ito; Tama Kanematsu (i-Perception, 2024)
Transient-induced fading is a phenomenon where a peripheral target perceptually fades when a surrounding object is flashed. It has been suggested that the transient-induced fading could be affected not only by the lower-level factors such as the luminance contrast change, but also by the higher-level factors such as Gestalt grouping by similarity. In the present study, Experiment 1 investigated whether the perceptual fading of a visual target could be strongly induced when a ring area surrounding the target with high luminance contrast disappeared rather than appeared. Experiment 2 examined the effect of the (dis)appearance of a higher-level object (Kanizsa-type subjective contour) on the fading perception. Experiment 3 further investigated whether the rating of the perceived effortlessness of a subjective contour could be positively correlated with the fading duration of the target. Our results revealed that perceptual fading was mainly induced by the disappearance of fan areas inside black disks producing a subjective contour surrounding the target. Disappearance of a perceptual object at the representation level does not trigger the transient-induced fading even if a higher-level factor (e.g., grouping by similarity) affects the fading objects.